Semangat Belajar Siswa MI/SD dan Pengaruh Penggunaan Gadget - Yuningsih, Imas; Masyithoh, Siti (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
This research is motivated by the learning outcomes of students who pay less attention to their enthusiasm for learning. This is due to the lack of cooperation between teachers and parents in giving attention to students. With this, the researchers conducted a study to analyze students' learning enthusiasm and the effect of using gadgets, which are currently more popular than learning. The number of omissions in learning outcomes is believed to decrease due to excessive use of gadgets, causing dependence and hindering the learning process with enthusiasm. This study used a descriptive qualitative method by collecting data through a library study that the researcher had done. The purpose of writing this journal article is so that researchers or readers can find out how students are enthusiastic about learning and the effect of using gadgets on student enthusiasm for learning. The results of this study prove that students' enthusiasm for learning is not only due to the influence of the daily use of their gadgets, but most likely also caused by other things such as the teaching methods and strategies used by the teacher are not appropriate and efficient for students.